Technology-Enabled Supply Chain Finance for Small and Medium Enterprises is a Major Growth Opportunity for Banks - Saleem, Qamar; Hommes, Martin; Sorokina, Aksinya (International Finance Corporation, Washington, DC, 2018)
In most emerging markets, small and medium enterprises (SMEs), lack access to the credit and liquidity they require for their daily working capital needs. This is partly due to the fact that the credit risk of such businesses is typically difficult to assess and their working capital needs are unpredictable. In most countries these businesses operate primarily in the retail and wholesale trade segments, and banks have generally not done enough to finance their domestic or international trade operations, especially open account transactions. Supply chain finance structures offer an alternative solution to finance the trade flows of these enterprises, with benefits for all stakeholders, including large enterprises, their SME trade counterparts, and financial institutions. This type of financing helps banks extend working capital finance to SMEs by leveraging commercial and trust relationships between the SMEs and corporates; it helps large corporates improve their working capital management and decreases supply chain disruptions; and it enables banks to better assess, measure, and manage the risks of extending financing to SMEs.